NEUTRON INDUCED 55Mn REACTION IN THE ENERGY RANGE 0.001 MeV TO 40 MeV - Rahman, A. K. M. Rezaur; Hoque Happy, Taslim; Ovi, Mustofa Khalid; Awal, Abdul; Bromuela, Mark Anthony; Akhand, MD. Jubayer Rahman; Chakraborty, Shyamal Ranjan; A. K. M. Moinul Haque Meaze, (Malaysian Journal of Science, 2023)
Neutron induced 55Mn reactions are evaluated in the energy range 0.001 MeV to 40 MeV using TALYS 1.95 computer code. During this evaluation, local and global parameterisations of Koning and Delaroche are used in nuclear optical model. Comparisons were made with experimental data, collected from EXFOR and other sources. Some optical model parameters (OMP) were needed to be adjusted for better agreement between theoretical calculations and experimental findings. Various evaluated libraries such as ENDF, JENDL etc. are being checked and compared with our evaluation. TALYS evaluation shows better agreement when parameters were adjusted.